A human vision inspired adaptive platform for one-on-multiple recognition. Issue 33 (5th April 2019) - Zhu, Zhiyang; Huang, Jianbin; Yan, Yun
Abstract : One-on-multiple recognition resembling human vision generation is built through the conjunction of an ICT-bearing amphiphile with different metal ions. Abstract : The fluorescence of a coordinative moleculeDCM displaying an intramolecular charge transfer (ICT) effect is regulated by several metal ions. TheseDCM –metal complexes were adopted to recognize different chemicals, including the recognition of triethylenetetramine, thiol-containing amino acids, and H2 S upon bindingDCM with Zn 2+, Ag +, and Pb 2+, respectively. This is in analogy to the general mode of human trichromatic color vision.